Children's exposure to passive smoking in England since the 1980s: cotinine evidence from population surveys - Jarvis, Martin J (British Medical Journal, 2000)
OBJECTIVE: To determine whether children's exposure to passive smoking has changed since the late 1980s. DESIGN: Cross sectional surveys of nationally representative samples of secondary school children carried out between 1988 and 1998 by Office for National Statistics. SETTING: England. SUBJECTS: Secondary school children aged 11-15. MAIN OUTCOME MEASURES: Salivary cotinine concentrations in non-smoking children. RESULTS: Cotinine concentrations in all non-smoking children almost halved between 1988 and 1998, from a geometric mean of 0.96 (95% confidence interval 0.83 to 1.11) ng/ml in 1988 to 0.52 (0.43 to 0.62) ng/ml in 1998. This reduction was largely due to reductions in exposure in children from non-smoking households and to decreases in the percentage of parents who smoked. Children living with mothers or fathers who smoked experienced little reduction in exposure. CONCLUSIONS: Exposure to passive smoking among children in England has approximately halved since the late 1980s. This reduction is partly explained by the fall in the percentage of both mothers and fathers who smoke and is also likely to reflect reductions of smoking in public places. However, there is only limited evidence that children from smoking households have experienced a reduction in exposure through parents' avoidance of smoking in their presence.